Multi-annual investment plans of Wrocław in the years 2015–2019. Directions of spending on the way to achieving the city’s development goals - Rynio, Dorota (Wieloletni plan inwestycyjny Wrocławia w latach 2015–2019. Kierunki wydatkowania środków w drodze osiągania celu rozwoju miasta, 2015)
Socio-economic development of a city depends highly on investment policy and finance abilities for realized projects. Permanent supply of funds for that goal is very important and it is possible because of strategic programming of expenses in a long-term period. In the MIP 2015–2019 for Wrocław expenses are concentrated on: transport, renovations and rebuilding of streets and public transportation; education; and also other subdivision tasks. Planned expenses will reduce development barriers of the city, assuring consistency of projects realization and they can help in realization of socio-economic development strategy priorities. In the long term, the goals of the city development will be achieved. Consistent planning of the investment expenditure process affects the implementation of development and strategic challenges of the city, focuses funds on indicated tasks and allows for flexible redeployment of funds in the variable conditions of the global economy
Biblioteka Regionalisty, 2015, Nr 15, s. 93-102
Keywords: multi-annual investment plan; strategy; city; investments; investment policy; wieloletni plan inwestycyjny; strategia; miasto; inwestycje; polityka inwestycyjna